Sexual Abuse and Neglect during Childhood are Associated with an Increased Prevalence of Mental Health Problems among University Students in Surakarta, Indonesia - Putu Dian Apriandary, Ni; Muthmainah,; Setyaningrum, Rohmaningtyas Hidayah; Septiawan, Debree (Folia Medica Indonesiana, 2024)
Highlights:1. This study reiterates the long-term negative impact of childhood trauma on young adults' mental health.2. This study contributes to the prevention of mental disorders through the identification of risk factors associated with mental health problems. AbstractThe prevalence of mental health problems is a global public health concern. Young adults, such as university students, are highly vulnerable to the onset of mental health problems due to biological, psychological, and social factors. In particular, abusive and traumatic experiences during childhood may increase the risk of developing mental health problems during adulthood. The prevalence of child abuse cases in Indonesia is concerning. This abuse includes physical, emotional, and sexual abuse, in addition to neglect. This study aimed to assess the relationship between the occurrence of mental disorder symptoms during young adulthood and the preceding child abuse. A total of 191 undergraduate students in Surakarta, Indonesia, participated in this study. The participants completed the Child Abuse and Trauma Scale (CATS) for the evaluation of maltreatment experienced during childhood and adolescence as well as the Self-Reporting Questionnaire-20 (SRQ-20) for the measurement of mental health problem symptoms. The association of the degree of child abuse and trauma with mental health problems was analyzed using a logistic regression test, which was selected because the dependent variable (mental health problems) had binary outcomes. The level of statistical significance was set at p<0.05. We found that 33% of the participants reported mental health problems. In addition, sexual abuse and neglect were found to be associated with mental health problems. The analysis of the sexual abuse variable revealed a statistically significant value of p=0.03, an odds ratio (OR) of 1.39, and a 95% confidence interval (CI) of 1.03-1.88. Additionally, the analysis of the neglect variable yielded comparable results with values of p=0.03, OR=1.26, and 95% CI=1.02-1.55. Our findings suggest that child abuse, particularly sexual abuse and neglect, may have a long-term deleterious impact on an individual’s mental health.